Dectin-1 Signaling Update: New Perspectives for Trained Immunity - Mata-Martínez, Pablo; Bergón-Gutiérrez, Marta; del Fresno, Carlos (Frontiers in Immunology, 2022)
The C-type lectin receptor Dectin-1 was originally described as the -glucan receptor expressed in myeloid cells, with crucial functions in antifungal responses. However, over time, different ligands both of microbial-derived and endogenous origin have been shown to be recognized by Dectin-1. The outcomes of this recognition are diverse, including pro-inflammatory responses such as cytokine production, reactive oxygen species generation and phagocytosis. Nonetheless, tolerant responses have been also attributed to Dectin-1, depending on the specific ligand engaged. Dectin-1 recognition of their ligands triggers a plethora of downstream signaling pathways, with complex interrelationships. These signaling routes can be modulated by diverse factors such as phosphatases or tetraspanins, resulting either in pro-inflammatory or regulatory responses. Since its first depiction, Dectin-1 has recently gained a renewed attention due to its role in the induction of trained immunity. This process of long-term memory of innate immune cells can be triggered by -glucans, and Dectin-1 is crucial for its initiation. The main signaling pathways involved in this process have been described, although the understanding of the above-mentioned complexity in the -glucan-induced trained immunity is still scarce. In here, we have reviewed and updated all these factors related to the biology of Dectin-1, highlighting the gaps that deserve further research. We believe on the relevance to fully understand how this receptor works, and therefore, how we could harness it in different pathological conditions as diverse as fungal infections, autoimmunity, or cancer.